2015
DOI: 10.12800/ccd.v10i29.551
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the acceleration, change of direction and jumping capacity between different ages soccer players

Abstract: ResumenLos principales objetivos de este estudio fueron analizar la capacidad de aceleración, capacidad de cambio de dirección (CODA), salto vertical (VJ) y salto horizontal (HJ) en futbolistas cadetes y juveniles y determinar las diferencias en estas cualidades en función de la categoría. La muestra total (n = 34) fue dividida en dos grupos, atendiendo a la categoría en la que competían. El grupo 1 (CAD, n = 17) competía en la Liga Vasca Cadete (15.12 ± 0.70 años), mientras que el grupo 2 (JUV, n = 17) lo hac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…In fact, Maulder and Cronin (2005) point to the greater specificity of HJ tests in comparison with VJ tests. In this line, Santiago et al (2015) observed differences in HJ between junior and under-15 category players (p < 0.01, d > 0.8, high). The fact that the G2B group did not score better results than the rest of the groups in our study indicates that there may be other factors which are more important in futsal like for example the individual technique of the player, team tactics, experience or psychological aspects among others.…”
Section: Discussionmentioning
confidence: 69%
“…In fact, Maulder and Cronin (2005) point to the greater specificity of HJ tests in comparison with VJ tests. In this line, Santiago et al (2015) observed differences in HJ between junior and under-15 category players (p < 0.01, d > 0.8, high). The fact that the G2B group did not score better results than the rest of the groups in our study indicates that there may be other factors which are more important in futsal like for example the individual technique of the player, team tactics, experience or psychological aspects among others.…”
Section: Discussionmentioning
confidence: 69%
“…Posteriormente, se evaluó la potencia del salto mediante la plataforma de contacto AXON JUMP y el programa AXON JUMP 4.0, diseñada para la evaluación de distintas capacidades mecánicas cinemáticas del deportista, entre ellas la capacidad de salto, determinando la altura de cada uno de los saltos verticales (Santiago, et al, 2015; Departamento Administrativo del Deporte, la Recreación, la Actividad Física y el Aprovechamiento del Tiempo Libre -Coldeportes, 2015). Los saltos usados se basan en el protocolo descrito por Bosco, et al (1983), cuya batería de pruebas de saltos verticales valoran las características funcionales y neuromusculares.…”
Section: Materiales Y Métodosunclassified
“…Antes de terminar, los cambios de dirección (CODA) son uno de los parámetros determinantes del rendimiento en jugadores de fútbol (Bangsbo, Mohr & Krustrup, 2006;Pardeiro & Yanci, 2017;Santiago, Granados, Quintela & Yanci, 2015) y en otros deportes (Yanci, Castillo, Vizcay, Pitillas & Iturricastillo, 2016), aunque no de forma exclusiva, ya que son necesarios también potencia aeróbica, fuerza y la velocidad (Yanci, García, Castillo & Rivero, 2014). Si bien las investigaciones en este campo se centran en etapas de rendimiento y población masculina.…”
Section: Introductionunclassified